Costs and beneftis of temporary contracts - Axel Engellandt (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2005)
Applying data from 13 waves of the Swiss Labor Force Survey (1991-2003) I assess costs and benefits of fixed-term contracts. First, I analyze the existence of a contract related wage gap and the effort response of temporary employees in terms of unpaid overtime hours. Second, I investigate whether workers' absence response to temporary contracts varies across types of absences. And third, I examine the impact of temporary contracts on accident rates. I find that temporary employees suffer a wage gap of 7 percent and provide about 45 percent more unpaid overtime hours than permanently employed persons. I find neither a significant impact in terms of total absences nor in terms of accidents even though the probability of receiving employer provided training is by 35 percent lower for temporary employees. Splitting total absences in two subcategories yields no significant impact of temporary contracts on absences due to accident and illness, but a significant positive effect on absences due to private reasons. The probability of absences due to private reasons is by 124 percent higher for temporary employees than for permanent employees. The results in terms of absences are not affected by including absences due to missing reasons in the analysis.
Keywords: J22; J28; J41; C23; C24; C25; 330; Temporary work; contract-related incentives; career concerns; effort; job search